Retracted: Effects of Methanolic Leaf Extract of Momordica charantia on Testicular Marker Enzymes and Gonadotrophic Hormones in Cadmium-induced Gonadotoxic Ratsretracted - Bamidele S. Ajilore; Olusegun O. Babalola; Olugbenga A. Ayannuga (International Journal of Phytomedicine, 2016)
Retracted: Effects of Methanolic Leaf Extract of Momordica charantia on Testicular Marker Enzymes and Gonadotrophic Hormones in Cadmium-induced Gonadotoxic Ratsretracted.